Government and politics in Pakistan - "Ahmad, Mushtaq" (Karachi, 1963)
In this second edition an attempt has been made to bring the book update. The first edition marked the end of the first phase in the political history of the country Martial Law was imposed while it was in the press, but no fresh evidence was brought to light to warrant a radical revision of the book. Only a brief account of the military regime was added towards the end as it was then only three months old. With minor changes the first part is more or less the original text of the first edition. In the second part the record of the Revolutionary Government in the field of Reform and Reorganisation, Economic Policy, Labour and Rehabilitation and Foreign Relations has been examined. An attempt has also been made to evaluate the impact of Martial Law, providing a background to the emerging political situation. The third part contains an analysis of the New Constitution, the role of the President and the National Assembly and attitudes of political parties and personalities towards the Constitution.
Keywords: Pakistan- Government and politics